Unveiling Ayam Betutu: Exploring the Rich Heritage and Tourist Experiences of Bali’s Iconic Culinary Delight on TripAdvisor - Sandi Wachyuni , Suci; Wuryo Handono , Felix; Lochan , Amarjiva; Wiweka, Kadek (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study conducts a sentiment analysis of customer reviews for Ayam Betutu Khas Gilimanuk Cabang Tuban on TripAdvisor, a leading platform for culinary and tourism references, to assess consumer perceptions in the digital era. While prior research has explored online reviews in the restaurant industry, few focus on heritage culinary establishments, leaving a gap this study addresses by analysing 421 reviews (2012–2024) across variables such as rating, comment, and region. Using RStudio, the data underwent text preprocessing (tokenisation, case-folding, stopword removal), sentiment labelling (positive, neutral, negative), and lexicon-based analysis, supplemented by word clouds and temporal trend evaluation. Findings reveal predominantly positive sentiment towards the restaurant’s signature Balinese ayam betutu, though areas like service, cleanliness, and ambience require improvement. Theoretically, the study highlights that product quality alone cannot sustain positive sentiment without complementary service excellence, while practical implications offer actionable strategies for heritage restaurants and regional gastronomy development, bridging digital analytics with culinary heritage preservation.